Cover Image. (20th February 2021) - Lee, Yoonjin; Shin, Kayoung; Shin, Kyong‐Oh; Yoon, Seokjeong; Jung, Juyeon; Hwang, Eojin; Chung, Hwa‐Jee; Hossini, Amir M.; Zouboulis, Christos C.; Baek, Min Jeong; Baek, Ji Hwoon; Chi, Young Min; et al.
Abstract : The cover image is based on the Original Article The Effect of High‐Intensity Focused Electromagnetic Procedure on Visceral Adipose Tissue: Retrospective Assessment of Computed Tomography Scans David Kent and Brian Kinney https://doi.org/10.1111/jocd.13952 .